Potensi Bacillus cereus dan Bacillus subtilis Menurunkan Kandungan Logam Fe dan Mn pada Air Asam Tambang - Rizqi Nadhirawaty; Yus Santo; Dhany Achmad Wicaksono; Moza Ajeng Azilla; Muhammad Reviand Ari; Rindiani Evitaningrum Waodthe Kaiya (Politeknik Pertanian Negeri Samarinda, 2022)
Acid mine drainage (AMD) with pH 2,56, also high concentration of Fe and Mn respectively 35 mg/L and 8,83 mg/L should be treated to prevent the pollution. AMD treatment can be done by adding bacteria. Bacillus cereus and Bacillus subtilis isolated from AMD sample using selective media agar. Each bacteria was added 5% and 10% to the 200 mL AMD sample separately. The result shows that the highest removal of Fe and Mn in AMD was 62.03% and 18.02% with 10% B. cereus. Meanwhile, with addition 5% B.subtilis shows the highest Fe and Mn removal respectively 41.91% and 16.79%. Therefore, these bacteria have potential to decrease Fe and Mn concentrations in AMD.